A study on the present status of lAS-II comparison group - Alim, Md. Abdul (Research and Evaluation Division, Brac, 2019)
The Research and Evaluation Division (RED) of BRAC has over the years been making efforts to evaluate the impact of Rural Development Programme (RDP) on its members through impact assessment studit:S (lASs). RED has already conducted two such evaluations : IAS-I and LAS-II. A Uurd lAS is now underway. The panel comparison group, for L-\S , had been formed during lhe first lAS to measure the effective impact of RDP interventions making comparison between Ulis group and RDP beneficiaries group. The present report anempts to provide a few necessary inputs to LAS-III by examining the present status of the comparison group that would be required for the study. Although sdet;tion of t;Omparison household group is of vital necessity for impact assessment studies, it has been found that impact srudies have been perennially pla.:,oued by the lack of availability of appropriate non-beneficiaries. This is because NGO penetration has been pervasive. The reasons for this are lbe phenomen.1l growth of micro credit and proliferation of NGOs. The objective of the study was to examine the present status of IAS-ll comparison group .md find out whether household members were stillli"ing in their villages and whether they were involved ~ith any GO!NGO programmes as well as to look into the reasons for joining with these programmes. The present report was based on a survey that was conducted on 239 comparison households spread in 10 upazilas and 10 districts. It showed that 95% (228) were still living in their respective villages which meant that migr:ltion was quite low. The survey 3lso revealed the ex"lent of NGO membership status of the comparison hous~!holds and found that 55% households were involved in various GO/NGO development programmes since 1996. Almost half of the households out of 55 % were involved with Grameen B:mk, 15% joined BRAC followed by Bangladesh Rural Development Board (BRDB), Proshik.l, ASA tmd several other snuller NGOs. Data on lenoot.h of involvement of rhe members involved in different GO/NGO programmes have pointed out certain defects in the selection of comparison group for L~-II by showing that 21% of the membrn were already involved in GO/NGO programmes when the lAS started. This weakness limited the impact assessment to some ex-tent. It was found that .t 1% households did not join GO/NGO programmes. However, 29% out of these were earlier associated with GOINGO programmes. Reasons that were cited by households who never joined GO/NGO programmes indude worry and tension of these households fearing failure in n!pa:ying loan installments and lack of scope for invesunent. Only ~<% households numbering ten were not found owing to migration to other villages or cities in search of work or otl\er reasons to survive and 1% households heads died during the period.